2001
DOI: 10.1051/0004-6361:20010931
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive optics $\vec{L}$-band observations of the Galactic Center region

Abstract: Abstract. L-band adaptive optics observations of the Galactic Center region have been performed in June 1999and May 2000 at La Silla with the 3.6 m telescope, using the ADONIS adaptive optics system. In June 1999, we used a dedicated infrared wave-front sensor, RASOIR. This paper reports on the photometry and astrometry of more than 40 stars. Thanks to additional adaptive optics K-band observations made at CFHT, colour-magnitude diagrams have been constructed to identify individual sources with various types o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2003
2003
2004
2004

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(63 citation statements)
references
References 43 publications
2
61
0
Order By: Relevance
“…Infrared Spectra of the IRS 13 and IRS 13N complexes.-The flux density originating in the IRS 13N region is dominated by the cluster of newly found compact sources. In previously published images of this region (e.g., Eckart et al 1995;Stolovy et al 1999;Paumard et al 2001;Clénet et al 2001;Maillard et al 2003), these were either not detected or not spatially resolved. From the NAOS/CONICA L-band images we estimate that only a maximum amount of 1 4 of the emission may be attributed to a more extended interstellar component.…”
Section: A Cluster Of Young Starsmentioning
confidence: 80%
See 3 more Smart Citations
“…Infrared Spectra of the IRS 13 and IRS 13N complexes.-The flux density originating in the IRS 13N region is dominated by the cluster of newly found compact sources. In previously published images of this region (e.g., Eckart et al 1995;Stolovy et al 1999;Paumard et al 2001;Clénet et al 2001;Maillard et al 2003), these were either not detected or not spatially resolved. From the NAOS/CONICA L-band images we estimate that only a maximum amount of 1 4 of the emission may be attributed to a more extended interstellar component.…”
Section: A Cluster Of Young Starsmentioning
confidence: 80%
“…The detailed comparison of the images shows that with the exception of the sources and , the IRS 13N objects are very red (Fig. 3) compared to other sources in the field (see KÀL colors given by Clénet et al 2001). The objects and could not be identified in the H-band image, resulting in lower limits for their HÀK colors.…”
Section: The New Ir-excess Sourcesmentioning
confidence: 94%
See 2 more Smart Citations
“…Recently, it has been shown that the center of the Milky Way is inhabited by a SMBH of ∼ 3.6 × 10 6 M (Schödel et al 2002;Ghez et al 2003). The entire central parsec is powered by a cluster of young and massive stars as the IRS 16 complex (Blum et al 1988, Krabbe et al 1995, Genzel et al 1996, Eckart et al 1999, Clénet et al 2001. In addition to the massive supergiants, a population of dust embedded objects associated with dust emission are also found in the Galactic Center stellar cluster as IRS 1, IRS 3 and also the IRS 21 and IRS 8 sources that have been identified as bowshock sources (Tanner et al 2002, Rigaut et al 2003.…”
Section: Introductionmentioning
confidence: 99%